Analisis Jalur Struktur Modal Dan Nilai Perusahaan Dengan Metode Trade Off Theory - Nana Umdiana; Cucu Nurjanah (Jurnal Riset Akuntansi Terpadu, 2020)
This study aims to determine the path analysis of capital structure and firm value with the trade off theory method in LQ45 companies listed on the Indonesia Stock Exchange Period 2016-2018. The study was conducted using quantitative methods with an associative approach. The study population numbered 59 companies and 29 companies were sampled using purposive sampling. The study was conducted at LQ45 companies listed on the Indonesia Stock Exchange Period 2016 to 2018. Data was collected with the 2016-2018 Financial Statement, and analyzed with SPSS version 25. Based on the results of the study it can be concluded that: 1) there is an effect of profitability on firm value 2) there is an influence company size on firm value 3) there is an effect of profitability on capital structure 4) there is an effect of firm size on capital structure 5) there is an effect of capital structure on firm value 6) there is no effect of profitability on firm value through capital structure 7) there is no influence on company size to the value of the company through capital structure.